THE LIFE AND LEGACY OF ERNEST AMORY CODMAN: A PIONEER OF OUTCOMES AND A FORERUNNER OF MODERN QUALITY MEASUREMENT SYSTEMS IN HEALTHCARE - Medarević, Aleksandar (Sanamed, 2025)
Ernest Amory Codman (1869–1940) was an American surgeon, reformer, and visionary whose work marked the beginnings of systematic quality measurement in medicine. The first part of this paper traces his life and career: his education at Harvard Medical School, his work at Massachusetts General Hospital, his conflicts with colleagues over his insistence on public reporting of outcomes, his founding of a private hospital, and the establishment of the Bone Sarcoma Registry—one of the first disease-specific registries in history. The second part of the paper analyzes his philosophy of the “End Result System” through a comparative table in which its core principles—patient monitoring, complication tracking, transparency, continuous improvement, and accountability—are compared with their modern equivalents, such as outcome indicators, national registries, public reporting systems, quality improvement (QI) methodologies, and health information systems. The paper concludes that Codman’s work represents both the biographical story of a persistent reformer and a conceptual foundation for modern quality measurement systems in healthcare.